Fatores inibidores do risco moral na demanda por consultas médicas eletivas - Maciel Junior, José Nazareno (2011)
The aim of this study is to identify and quantify the existence of moral hazard in the Market for Supplementary Health more specifically to a provider of health plans in the form of large Medical Cooperative, through the analysis of demand for medical electives. This study compares the behavior of between plans with and without moderating factors, such as: co-participation and input port (gatekeeper). Was use of count models aiming to measure the overuse of medical services. Empirical data were collected from the Provider, treated as described and analyzed to test hypotheses about the efficiency of co-participation and input port (gatekeeper) in the reduction of moral hazard. The results revealed significant effects of these two instruments, showing a reduction of 0.306308 visits per year to the effect of coparticipation and up to 3.890354 visits per year in plans with gatekeeper. These results are controlled by the characteristics of users for age, sex, marital status, time plan, and usage history. In a direct extrapolation, this would represent an over-cost of about $ 290.000,00 (+ 487,42%) if all beneficiaries to raise their plans without any inhibiting factor.